RENTAL PROCEDURES AND LEGAL CHALLENGES IN THE WEDDING ORGANIZER INDUSTRY: OWNERS' AND PRACTITIONERS' PERSPECTIVES - Batari Mulya; Mochammad Tanzil Multazam (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Marriage is an important moment that requires careful planning and involves many vendors, but it can lead to legal issues that harm clients, vendors, and wedding organizers (WO). Some common legal issues include discrepancies in goods, delayed returns, damage to items, and contract misunderstandings. Method: This study uses in-depth interviews with experienced practitioners and references from trusted sources. Results: Interviews with sources reveal that clear agreements and good communication can prevent legal problems. The findings show that while the wedding organizer industry offers significant profits, legal challenges such as payment issues between vendors and WOs, as well as event cancellations, are common. Solutions to reduce legal risks include drafting detailed contracts, ensuring effective communication, and implementing procedures in accordance with the law to create harmonious relationships and minimize disputes. Novelty: The study highlights the importance of legal awareness and preventive legal strategies in the wedding organizer industry by emphasizing structured agreements, communication, and legal procedures to minimize disputes among clients, vendors, and wedding organizers.